Pengaruh Intervensi terhadap Kepatuhan Penggunaan Analgesik Opioid dan Skala Nyeri Pasien Kanker - Rurynta Ferly Shavira; Retnosari Andrajati; Risani Andalasia Putri (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2021)
Cancer pain patients who receive opioid analgesics need to be given educational interventions to increase patient knowledge that can have a positive impact on patient adherence, especially in outpatients who will take opioid analgesics without being accompanied by professional. To maximize the effectiveness of the intervention, it is necessary to know the relationship between the intervention to adherence and the intervention to the pain scale. This study aimed to analyze the effect of the intervention and other factors on patient adherence in using opioid analgesics and the cancer pain scale. This study was conducted at Dharmais Cancer Hospital from March-April 2021 using a quasi-experimental design in the form of nonequivalent control group. In this study, the method used are pill count to measure adherence and NRS (Numerical Rating Scale) to measure the pain scale. Measurement of adherence using pill count was conducted after the intervention, but the measurement of the pain scale was conducted before and after the intervention. A total of 134 respondents were divided into 2 intervention groups, namely the counseling group and the digital booklet group. The results of the multivariate analysis showed that there was no variable that interfered with the relationship between the intervention and respondent's adherence. The adherence of respondents who received counseling was 4 times higher than the respondents who received digital booklet. From the results of this study, it can also be concluded that the more obedient the respondent is, the lower the pain scale.